Пейзажи "Путешествия в Арзрум во время похода 1829 года" как отражение истоков реализма в художественной системе А.С. Пушкина - Иванова, Н.П. (Культура народов Причерноморья, 2003)
In the article are examining the sources of realism in Pushkin`s artistic system. As an example are using descriptions of Caucasus in the “Journey to Arzrum during campaign in 1829”. Method of contrast is researching as a fundamental method of creation of expressiveness.